Impairments of social interaction in a valproic acid model in mice - Ukezono, Masatoshi; Kasahara, Yoshiyuki; Yoshida, Chihiro; Murakami, Yuki; Okada, Takashi; Takano, Yuji (Frontiers in Behavioral Neuroscience, 2024)
A rodent autism spectrum disorder (ASD) model based on prenatal exposure to valproic acid (VPA) is widely recognized as a prominent model. In this study, we focused on social attention in the VPA model of ASD. In male C57BL6/J mice, attentional behaviors towards conspecifics were examined through reaching tasks until ten weeks of age. On embryonic day 12.5, pregnant mice underwent a subcutaneous injection of 600 mg/kg VPA sodium salt dissolved in 0.9 % saline solution (VPA group) or saline solution alone (Sal group) into their neck fat. Thirty-six mice-9 each in the VPA and saline groups, and eighteen partnersunderwent training in reaching behavior. Subsequently, we examined whether the VPA or Sal group demonstrated focused attention toward their partners during reaching tasks. A two-way analysis of variance (ANOVA) (condition [VPA/Sal] × situation [face-to-face /not paying attention ]) was conducted on the average success rate of the situation. Additionally, we measured the duration of sniffing behavior between pairs of mice in an open field arena before reaching task four and eight weeks of age. The pairs were constructed by pairing a VPA or Sal group mouse with its partner, with the objective of facilitating initial encounters between the mice. A one-way ANOVA was conducted on the average duration of sniffing in the four and eight weeks, respectively. The analysis revealed an interaction between condition and situation in the reaching task (F (1,28) = 6.75, p = .015, ηp 2 = .19). The simple main effect test exhibited that the "not paying attention" rate was significantly higher than that of the "face-to-face" in the VPA group (p < .01). The results revealed a significant difference in the average duration of sniffing behavior (F (3,32) = 4.12, p < .05, ηp 2 = .28). Multiple comparisons using the Bonferroni method revealed significant differences in the sniffing duration from the partner towards the VPA mouse and from the partner towards the Sal mouse (p < .05). By focusing on social attention and exploring various ASD models, insights can be gained from the neural mechanisms underlying gaze abnormalities during social interaction in individuals with ASD.